PENEGAKAN DAN PERLINDUNGAN HUKUM TERHADAP KORBAN PELECEHAN SEKSUAL SECARA VERBAL - Puspita, Melati Intan; Budiarsih, Budiarsih (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Criminal provisions are regulated in the Criminal Code. Formed by the legislature to provide protection against immoral acts or criminals, and behavior in the form of unethical words or actions against good morals. This is because it relates to the sex life habits of the local population, contrary to the notion of community validity in the area of ??sex life where words are spoken and actions are performed. This investigation is a normative legal investigation or a normative legal investigation. Normative legal investigations, or normative legal investigations, are investigations that discuss legal principles, the legal system, the scope of legal synchronization, legal history, and legal comparisons. From the authors' findings, we can conclude that the initial prosecution of verbal sexual harassment has not been successful because of the obstacles in the process. These restrictions include factors of the law itself, factors of law enforcement, and community factors. Second, crime prevention occurs in several stages: development, implementation, and execution. The Criminal Procedure Code also needs to consider two main points of criminal law policy. Protection of victims of verbal violence by Catcalling is Article 5 of Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims, Article 5 of Law Number 31 of 1999. This can be done through rights contained in edition 39. TPKS Rights Law no. 12 Year 2022